Neural basis for pheromone signal transduction in mice - Murata, Ken; Itakura, Takumi; Touhara, Kazushige (Frontiers in Neural Circuits, 2024)
Pheromones are specialized chemical messengers used for inter-individual communication within the same species, playing crucial roles in modulating behaviors and physiological states. The detection mechanisms of these signals at the peripheral organ and their transduction to the brain have been unclear. However, recent identification of pheromone molecules, their corresponding receptors, and advancements in neuroscientific technology have started to elucidate these processes. In mammals, the detection and interpretation of pheromone signals are primarily attributed to the vomeronasal system, which is a specialized olfactory apparatus predominantly dedicated to decoding sociochemical cues. In this mini-review, we aim to delineate the vomeronasal signal transduction pathway initiated by specific vomeronasal receptor-ligand interactions in mice. First, we catalog the previously identified pheromone ligands and their corresponding receptor pairs, providing a foundational understanding of the specificity inherent in pheromonal communication. Subsequently, we examine the neural circuits involved in processing each pheromone signal. We focus on the anatomical pathways, the sexually dimorphic and physiological state-dependent aspects of signal transduction, and the neural coding strategies underlying behavioral responses to pheromonal cues. These insights provide further critical questions regarding the development of innate circuit formation and plasticity within these circuits.